2020
DOI: 10.7127/rbai.v14n101152
|View full text |Cite
|
Sign up to set email alerts
|

Available water content for the management of irrigated crops in the northwestern region of Parana State

Abstract: Pedotransfer functions of the available water content (AWC) as a function of the granulometric variability may contribute to irrigation management. The aim of this study was to generate pedotransfer functions to estimate soil water retention curves and AWC fractions in soils in the Northwestern Region of Parana State (Brazil) to manage water in irrigated systems with different crops. In 2016, soil sampling was carried out for granulometric determinations (total sand content, five sand fractions, silt, clay), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Soil organic carbon and moisture (Table 1) are within the variability of soils in the Northwest region of the state of Paraná, Southern Brazil (Fidalski and Helbel Junior, 2020). The organic carbon content remained statistically equal between the three sampling positions for the three soils after 8-18 years after the establishment of the orange orchards, in line with Conant et al (2017).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Soil organic carbon and moisture (Table 1) are within the variability of soils in the Northwest region of the state of Paraná, Southern Brazil (Fidalski and Helbel Junior, 2020). The organic carbon content remained statistically equal between the three sampling positions for the three soils after 8-18 years after the establishment of the orange orchards, in line with Conant et al (2017).…”
Section: Discussionmentioning
confidence: 60%
“…Approximately 8 % of Brazilian land area is characterized as sandy soil, corresponding to the sand, loamy-sand or sandy-loam textural classes up to a depth of 0.75 m or more, belonging to the Neossolos Quartzarênicos (Arenosols), Latossolos (Ferralsols) and Argissolos (Lixisols), according to the Brazilian System of Soil Classification (Donagemma et al, 2016). In the Northwest region of the state of Paraná, Southern, there are approximately 30,000 km 2 of sandy soils, corresponding to 16 % of the State's area (Fidalski and Helbel Junior, 2020). These soils are formed by rocks belonging to the Caiuá Group, which is formed by the Paraná River, Goioerê and Santo Anastácio geological formations (Etchebehere et al, 2007), and referred to locally as the Arenito Caiuá.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the low water holding capacity of sandy soils, even proper soil management and fertilization practices may compromise crop yields under water deficit (Fidalski & Helbel Junior 2020). Volsi et al (2020) carried out experiments in the northwest Paraná state with different crops associated with the no-tillage system and, because of the soil water availability, concluded that there is low profitability for the bean cultivation in this region without irrigation.…”
Section: Abstract Resumomentioning
confidence: 99%